Nigeria’s National Interest and Liberation Diplomacy in the Context of Africa - PIATE, Sunny Mene; NEKABARI, Dumle Callistus; KIA, Bariledum (Socialscientia: Journal of Social Sciences and Humanities, 2025)
Liberation diplomacy is the diplomatic strategy used by countries or groups fighting for independence from colonialism, tyranny, or any other kind of dominance. Achieving political emancipation via diplomatic means is what it entails. Sanctions, embargoes, and the cutting of diplomatic links are significant instruments in the diplomatic isolation of the repressive government. Ultimately, liberation diplomacy boils down to promoting independence and self-determination via diplomatic channels. When it comes to the liberation of African nations from colonial domination, Nigeria has been a vital player. Knowing that liberation diplomacy from Nigeria was vital in the battle against apartheid in South Africa and across Africa is crucial to decolonisation efforts. But there have been complications and areas of contention about its success, as there are with any foreign strategy. With this background, the research endeavours to place liberation diplomacy, a thrust of Nigeria’s foreign policy, inside the framework of Nigeria’s national interest. In light of these factors, the research aims to determine how much liberation diplomacy impacted Nigeria’s internal development objectives. Political realism provides the theoretical framework for understanding the conversation. Justice and rights arguments must be based on strategic considerations that are in line with the interests of state players in the international system, and here is where the theory comes in handy for the research. Study results showed that Nigeria, like any country based on a mechanical structure, would have weak national interests and, thus, would not be able to reap the rewards of sacrifice in its foreign relations. The fact that other players in the international system have heavily penetrated Africa and Nigeria’s power standing are the reasons why the reciprocity dynamics seem to have worked havoc against Nigeria. According to the research, Nigeria should prioritise both its internal demands and its obligations on the continental level. That is, Nigeria need to direct its foreign policy efforts inward so that it might contribute to the country’s prosperity.